Analysis of the Principle of Notary Independence in Notarial Deed Making in Review of the Notary Position Law and the Notary Professional Code of Ethics - Supriyanto, Agus Supriyanto; Sulistyono , Adi (CV. Inara, 2024)
The position of notary is an office of trust and is a noble profession (officum nobile), in carrying out the duties of his office the notary is regulated by Law No. 30 of 2004 concerning the office of notary which has been amended by Law No. 2 of 2014 concerning the Office of Notary and also regulated in the Code of Ethics for the Notary Profession. in carrying out the duties of a notary has obligations and authorities, one of which is the obligation to be independent. In this study aims to analyze how the ideal regulation so that the principle of notary independence in making deeds can be carried out properly. this research is a notmative legal research where the author approaches the problem by studying the provisions of the applicable law and studying the views and doctrines in legal science relating to the obligation of notaries to act independently in carrying out their job duties. The Notary Position Law has actually provided a legal framework to support the independence of notaries in carrying out their duties. However, the application of this principle of independence in daily practice may depend on how the notary complies with the law and professional ethics and there is still a legal gap where there is no specific regulation relating to the independence or impartiality of notaries. The definition of notary independence in the Notary Law and the notary code of ethics is very limited, with no classification regarding the form of the law, as with the independence of judges who have a clearer classification, it would be better if the code of ethics of the notary profession explains in more detail regarding the independence of notaries in terms of structural, functional, financial, and independence in carrying out the duties of the office of notary.